Coping Strategies in Migraine without Aura: A Cross-Sectional Study - Antonio Russo; Gabriella Santangelo; Alessandro Tessitore; Marcello Silvestro; Francesca Trojsi; Antonio De Mase; Federica Garramone; Luigi Trojano; Gioacchino Tedeschi (Behavioural Neurology)
Background. In the context of a causal relationship between stress and migraine, coping strategies are aimed at managing stressful life events and reducing the distressing emotions connected to them. Methods. Sixty-one consecutive patients with migraine without aura (MwoA) and sixty-one healthy controls (HCs) completed three self-report questionnaires assessing a broad range of coping (cognitive and behavioural) strategies: the Coping Orientation to Problems Experienced (COPE), the Coping Inventory for Stressful Situation (CISS), and the Proactive Coping Inventory (PCI). Moreover, the Perceived Stress Scale (PSS), a scale measuring self-perception of stress, global cognitive functioning, depressive symptoms, apathy, state, and trait anxiety, was administered to all participants. Results. No significant difference was found on the scales and subscales of PCI and CISS as well as in the PSS between MwoA patients and HCs. However, the two groups showed different scores in the subscale “turning to religion” of COPE (22.08±5.19 in migraineurs vs. 24.70±4.44 in HCs, p=0.003). A significant negative correlation of the turning to religion score with the HIT-6 score was found. Conclusions. The present study revealed that MwoA patients show a significantly reduced use of the “turning to religion” approach, an emotion-focused coping strategy. Although migraine patients appeared to be less oriented to transcendent (that means a reduced utilization of an adaptive coping strategy), they did not perceive daily living as more stressful than HCs. Finally, the reduced utilization of the “turning to religion” coping strategy is associated with a great impact of migraine on ability to function on the job or at school, at home, and in social situations in migraine patients.